Mental Health, Subjective Well-Being, and Academic Performance in Chilean Schoolchildren Who Are Part and Are Not Part of the School Inclusion Program - Yasna Chávez-Castillo; Rafael Zapata-Lamana; Caterin Diaz-Vargas; Lorena Antileo-Miño; Lilian Castro-Durán; Jaime Vásquez-Gómez; Maria Antonia Parra-Rizo; Igor Cigarroa (MDPI AG, 2023)
Inclusive education acknowledges and values the capabilities and needs of every student. Exploring their perceptions of psychosocial variables and academic performance can significantly enhance inclusive practices and improve overall school performance, particularly for students with special educational needs (SEN). This study aimed to assess mental health, subjective well-being, and academic performance among students in the school inclusion program (SIP) and those not in the program. Conducted as an analytical cross-sectional study, this research endeavor entailed the utilization of a probabilistic, stratified sampling approach designed to ensure community representativeness. The study sample encompassed a cohort of 730 school students aged between 10 and 15 years (M = 12; SD = 1.3 years) representing five different public schools in the Biobío region, all integrating SIPs into their educational structure. Student assessments involved the Rosenberg Self-Esteem Scale, Beck Anxiety Inventory, and Subjective Happiness Scale. Additionally, their academic performance was measured based on grade point averages (GPAs) and final accumulated grades in language and literature as well as mathematics. Students enrolled in the SIP obtained lower scores in the self-esteem, anxiety, and happiness assessments along with poorer academic performance compared to their non-SIP counterparts. Consequently, students participating in the SIP displayed lower levels of mental health and subjective well-being along with inferior academic performance in contrast to their non-participating counterparts. These findings are alarming, as SIP implementation is a key strategy for promoting inclusive education in Chile and enhancing the learning of all students, especially those with SEN.